A MARKETING PROPOSAL FOR THE THE CENTRE FOR SCIENTIFIC DOCUMENTATION AND INFORMATION - THE INDONESIAN INSTITUTE OF SCIENCES (PDII-LIPI) - Endang Ernawati (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 1996)
Product and services from PDII-LIPI should be marketted with an appropriate and carrefull planing for the sake of the institution's success and use's satisfaction.